HYDROLOGICAL ANALYSIS OF THE CIKAPUNDUNG WATERSHED, TAMANSARI BALUBUR AREA OF BANDUNG, WEST JAVA, INDONESIA - Rohmat Rohmat; Juang Akbardin; Johar Maknun (Journal of Development and Integrated Engineering, 2021)
AbstractCikapundung River is one of the rivers that divide Bandung City which functions as the city's main drainage, the general use of Cikapundung River water is for drinking water (PDAM Dago Pakar and PDAM Badak Singa), hydropower (Pakar and Cilengkung), and irrigation. The number of activities and utilization of the Cikapundung river in quantity is at risk of causing flooding which is influenced by various factors. Therefore, it is necessary to analyze the flood discharge to determine the value of the planned flood discharge in the Cikapundung River. The purpose of this study was to analyze flood discharge using empirical methods on the Cikapundung river in the Tamansari area in the context of flood control efforts. The analysis carried out is a hydrological analysis which includes an analysis of maximum rainfall using the frequency distribution method type Gumbel, Haspers, Weduwen, and Log Pearson, and a design flood discharge analysis using the Rational Method. Based on the results of the analysis of the highest discharge, Rational Gumbel with a return period of 2 years 5,076 m3/s, a return period of 5 years 8,371 m3/s, a return period of 10 years 10,553 m3/s, a return period of 20 years 12,645 m3/s, 25 year return period 13,097 m3/s, 50 year return period 15,354 m3/s, 100 year return period 17,384 m3/s, 150 year return period 518,395 m3/sec. Efforts that can be made in flood control efforts are restoration or rearrangement of the environment around the Cikapundung river border. Keywords: Cikapundung Watershed Hydrological Analysis, Flood Discharge Analysis, Empirical Method